Experimental study on flow instability for downward flow in a narrow rectangular channel with flow pattern transition. (May 2020) - Zhang, Xue; Feng, Wenpei; Zhang, Jie; Guo, Simao; Ding, Wenjie; Chen, Hongli
Abstract: The flow instability of downward flow in a narrow rectangular channel was experimentally investigated with visualization under low pressure, low speed flow and two-side heated conditions. The onset of flow instability (OFI) was obtained by decreasing the flow rate with constant heating power and occurred at the lowest point of the pressure drop-mass flow rate curve. It was found that decreasing the inlet temperature and heating power or improving the pressure can stabilize the system. Besides, the flow pattern transition at OFI was divided into two types, the one is from the jammed gas column flow to the inverse annular flow, the other one is directly from the bubble flow to the inverse annular flow. The type of flow pattern transition with jammed gas column flow is more likely to occur for lower inlet temperature, lower heating power and higher pressure. A new empirical correlation which considering the effect of pressure was proposed to predict OFI since the empirical correlations for upward or horizontal flow don't apply downward flow, and it shows very good peformance for the present experimental data. In addition, a criterion for classifying what type of the flow pattern transition was obtained.